Regulatory Takings and the Environment : the Impact of Property Rights Litigation. - Botello-Samson, Darren (Recht und Gesellschaft., 2010)
Botello-Samson reconceptualizes the relationship between regulatory agencies and regulatory takings litigation. By analyzing the impact of such litigation on the implementation of two federal environmental statutes, the Surface Mining Control and Reclamation Act and the Endangered Species Act, the author uncovers institutionalized characteristics of these regulatory regimes which insulate policy decision-making from the forces of a chilling effect. While these characteristics do not prevent a chilling effect, they do direct an understanding of regulatory takings litigation away from a total fo.